India : An Apartheid State - Junaid Ahmad (Karachi AJA Publishers, 2017)
India presents itself as a secular country. India is a Hindu state with a caste system which basically promotes inequality and apartheid in its true sense. The lower caste Hindus are considered untouchables and as such have no right to live. The Hindu State also treats followers of other religions as untouchables having limited rights. There have been thousands of riots in India since its establishment in 1947. These have included; Upper Caste Hindus vs Dalit riots; Hindu-Muslim riots, Hindu- Christian riots, Hindu-Sikh riots, atrocities committed in Indian-held Kashmir, Nagaland, Mizoram, and other places. Maltreatment of women, infanticide of girls and abortions also reflect the Hindutva approach to women. India destabilises its neighbours, created Bangladesh, meddled in the internal affairs of SriLanka and Nepal and continues to promote terrorism in Karachi and Balochistan. The support of the West enjoyed by India is perhaps attributable to the existence and promotion of eroticism, anti- Muslim posture and lately, the West is also using India against China and hence its support. Junaid Ahmad has collected a wide-range trove of facts, mostly from Indian, British and American sources, that expose the hollow secularism based on chicanery and deception through which present-day India constantly tries to befool the world.
Include Illustrations, Index, Glossary, Bibliography and Maps
Keywords: Asia And India History